Unveiling the veil of lactate in tumor-associated macrophages: a successful strategy for immunometabolic therapy - Tao, Hongxia; Zhong, Xuansheng; Zeng, Anqi; Song, Linjiang (Frontiers in Immunology, 2023)
Lactate, traditionally regarded as a metabolic waste product at the terminal of the glycolysis process, has recently been found to have multifaceted functional roles in metabolism and beyond. A metabolic reprogramming phenomenon commonly seen in tumor cells, known as the "Warburg effect," sees high levels of aerobic glycolysis result in an excessive production of lactate. This lactate serves as a substrate that sustains not only the survival of cancer cells but also immune cells. However, it also inhibits the function of tumor-associated macrophages (TAMs), a group of innate immune cells ubiquitously present in solid tumors, thereby facilitating the immune evasion of malignant tumor cells. Characterized by their high plasticity, TAMs are generally divided into the pro-inflammatory M1 phenotype and the pro-tumour M2 phenotype.Through a process of 'education' by lactate, TAMs tend to adopt an immunosuppressive phenotype and collaborate with tumor cells to promote angiogenesis. Additionally, there is growing evidence linking metabolic reprogramming with epigenetic modifications, suggesting the participation of histone modification in diverse cellular events within the tumor microenvironment (TME). In this review, we delve into recent discoveries concerning lactate metabolism in tumors, with a particular focus on the impact of lactate on the function of TAMs. We aim to consolidate the molecular mechanisms underlying lactate-induced TAM polarization and angiogenesis and explore the lactate-mediated crosstalk between TAMs and tumor cells. Finally, we also touch upon the latest progress in immunometabolic therapies and drug delivery strategies targeting glycolysis and lactate production, offering new perspectives for